BgFas1: A fatty acid synthase gene required for both hydrocarbon and cuticular fatty acid biosynthesis in the German cockroach, Blattella germanica (L.). (September 2019) - Pei, Xiao-Jin; Chen, Nan; Bai, Yu; Qiao, Jian-Wen; Li, Sheng; Fan, Yong-Liang; Liu, Tong-Xian
Abstract: Insect cuticular hydrocarbons (CHCs), the evolutionary products of aquatic hexapod ancestors expanding to terrestrial environment, are deposited on the surface of insect integument and originally functioned primarily as waterproofing agents. CHCs are derived from the conserved fatty acid synthesis pathway in insects. However, the pivotal fatty acid synthase (FAS) involved in hydrocarbon (HC) biosynthesis remains unknown in many insect orders including the primitive Blattodea. Here, we investigated functional FAS genes that modulate cuticular lipid biogenesis in the German cockroach, Blattella germanica (L.). Based on our full-length transcriptomic data and the available genomic data, seven FAS genes ( BgFas1–7 ) were identified from B. germanica . Tissue-specific expression analysis revealed that BgFas1, BgFas3, BgFas4 and BgFas7 were highly expressed in the integument, whereas BgFas2 was dominantly expressed in the fat body. BgFas5 /6 mRNA was almost negligible in the tested tissues. Systemic RNAi screen was performed against BgFas1–7, we found that only RNAi knockdown of BgFas1 caused a dramatic reduction of methyl-branched HCs (mbHCs) and a slight decrease of straight-chain HCs (scHCs) for both internal and external HCs. Significant reduction of cuticular free fatty acids (cFFAs) was also detected within BgFas1 -repressed cockroaches, while repression of CYP4G19 resulted in dramatic increase of cFFAs. Moreover, we found that BgFas1 mRNA levels were correlated with insect molting cycles, and could be induced by long-term mild dryness treatment. Furthermore, desiccation assay revealed that BgFas1 suppression accelerated water loss and led to early death of cockroaches under desiccation. Our results indicate that BgFas1 is necessary for both HC and cFFA biosynthesis in B. germanica . In addition, our study also confirms that cuticular lipids, particularly mbCHCs, are critical for desiccation resistance in B. germanica . Graphical abstract: Image 1 Highlights: RNAi of seven FAS family members within B. germanica identified BgFas1 as the functional gene involved in HC biogenesis. RNAi knockdown of BgFas1 dominantly reduces mbHCs within B. germanica. RNAi knockdown of BgFas1 simultaneously reduces cFFAs in B. germanica. Expression levels of BgFas1 can be induced by long-term dryness or insect molting. Knockdown of BgFas1 accelerates water loss rate and results in an early death for cockroaches under desiccation stress.